STUDI TENTANG MOTIVASI PESERTA DIDIK DALAM PEMBELAJARAN PENJAS ORKES DI SMP KARTIKA I-7 PADANG TIMUR - Alfon Meirony; Salamat Simanjuntak (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
In this study, the problem raised is the low motivation of learners in the learning of Physical Education of Sport And Health where in SMP Kartika I-7 Padang are many students that are not serious in doing sports activities which are taught and there is also a fear scolded by the teacher, so that Learners follow the sport with forced. The type of this research is descriptive, and it is with the student population of 496 people. Sampling technique is Stratified Proportional Random Sampling, where sample is taken at 10% of each class strata, obtained sample of 50 people. The instrument used for data collection is by questionnaire distribution on selected respondents. The research questions are: 1) How big is the intrinsic motivation of learners to the learning of Physical Education of Sport And Health in SMP Kartika I-7 Padang Timur. 2) How big is it the extrinsic motivation of learners toward the Physical Education of Sport And Health learning in SMP Kartika I-7 Padang Timur. The analysis data using descriptive statistics with frequency tabulation. Based on the results of the analysis can be concluded that the research shows that the intrinsic motivation is obtained with the achievement rate of 74.5%. This means that the intrinsic motivation which the learners have on the learning of Physical Education of Sport And Health is in a good category. As for the extrinsic motivation is obtained with a level of achievement of 67.8% that is categorized well. Thus, the intrinsic and extrinsic motivations of the learners are in good category. To obtain a level of achievement is categorized very well need to be increased their motivation, both from within the learners (intrinsic) and those coming from outside the learners (extrinsic).